2024
DOI: 10.1002/prp2.1197
|View full text |Cite
|
Sign up to set email alerts
|

Induction of hepatic CYP3A4 expression by cholesterol and cholic acid: Alterations of gene expression, microsomal activity, and pharmacokinetics

Genki Minegishi,
Yuka Kobayashi,
Mayu Fujikura
et al.

Abstract: Human cytochrome P450 3A4 (CYP3A4) is a drug‐metabolizing enzyme that is abundantly expressed in the liver and intestine. It is an important issue whether compounds of interest affect the expression of CYP3A4 because more than 30% of commercially available drugs are metabolized by CYP3A4. In this study, we examined the effects of cholesterol and cholic acid on the expression level and activity of CYP3A4 in hCYP3A mice that have a human CYP3A gene cluster and show human‐like regulation of the coding genes. A no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…The expression and activities of CYP‐enzymes are influenced by various factors, including genetics, diet, environment, and ethnicity. 9 , 26 It is valuable to explore data for Chinese outside of China. An analysis of gene polymorphisms among Chinese, Malays, and Indians in Singapore showed that pharmacogenetics of drug‐metabolizing enzymes in Asian populations differed significantly from Caucasian and African populations.…”
Section: Discussionmentioning
confidence: 99%
“…The expression and activities of CYP‐enzymes are influenced by various factors, including genetics, diet, environment, and ethnicity. 9 , 26 It is valuable to explore data for Chinese outside of China. An analysis of gene polymorphisms among Chinese, Malays, and Indians in Singapore showed that pharmacogenetics of drug‐metabolizing enzymes in Asian populations differed significantly from Caucasian and African populations.…”
Section: Discussionmentioning
confidence: 99%